Forest fire monitoring system - Khatir Kabashi, Shihabuddin Kabashi (2022)
The world's environmental concerns have never been larger or more complicated than they are now. Natural catastrophes have grown drastically in frequency and scale over the last few decades, threatening global regions covered by forests and urban woods. Forest fires on a large scale are one of the most dangerous natural disasters influencing climate change and human lives all over the planet. As a result, well-planned and closely coordinated effective preventive, early warning, and response techniques are required to limit their effects on people and the environment. This study describes a smart forest fire monitoring system that may be used in early fire warning systems and offers real-time temperature, humidity, flame, smoke, and location coordination monitoring. The system comprises of a single node and a gateway, and LoRa technology is the communication protocol implied in the system. The node has four sensors that measure temperature, relative humidity, gas levels in the environment, flame and location in order to evaluate the level of fire hazard and the likelihood of forest fires in a specific area. The sensor’s data is uploaded to the database and Cayenne cloud for notification. Using LoRa have an impact of longer transmission range between the sensor node and the gateway as well as it has low energy consumption compared to other communication protocols. Moreover, the system proved its durability under extreme weather conditions.